Comprehensive Review on Clostridium perfringens Control of Poultry Feed Storage - Ismiraj, Muhammad Rifqi; Mayasari, Novi; Firmansyah, Indra; Wulansari, Asri; Febrianto, Firman (Bulletin of Applied Animal Research, 2025)
This review aims to evaluate the role of feed storage practices in preventing the proliferation of Clostridium perfringens and its subsequent impact on poultry health and productivity. Clostridium perfringens is a Gram-positive bacterium capable of forming spores and producing toxins, and it is recognized as the causative agent of necrotic enteritis (NE). NE disrupts the gastrointestinal system of poultry, leading to impaired growth, increased mortality, and significant economic losses in the poultry industry. The primary factors influencing the growth of C. perfringens include feed storage conditions, specifically, prolonged storage duration, high humidity, and temperatures conducive to microbial proliferation. These conditions create an ideal environment for bacterial growth, particularly in feeds with high protein content. In addition, the bacterium’s inherent biological characteristics, such as its ability to form spores and produce toxins, further enhance its resilience and complicate control efforts. To mitigate the risk of contamination, this review outlines several control strategies. These include the optimal management of humidity and temperature, the reduction of storage duration, and the implementation of hermetic storage systems. Moreover, interventions such as the inoculation of lactic acid bacteria, and the targeted use of organic acids, probiotics, and mycotoxin binders, have proven effective in indirectly suppressing the growth of C. perfringens. A rigorous sanitation program is also emphasized to minimize cross-contamination. Ultimately, these measures are expected to enable farmers to maintain feed quality, enhance poultry health, and achieve more efficient and sustainable poultry production. Keywords : Clostridium perfringens, poultry production, feed storage, necrotic enteritis.